Nanostructured films of PM6 and Y6 and their assembly using Langmuir–Schaefer technique - Medina, Maria E． R． S． [UNESP]; Ferreira, Nyara D. [UNESP]; Junior, Luiz A． R． [UNESP]; Borro, Marcelo S. [UNESP]; Simõis, André V． S． [UNESP]; Maximino, Mateus D. [UNESP]; Constantino, Carlos J． L． [UNESP]; Hiorns, Roger C.; Braunger, Maria L. [UNESP]; Olivati, Clarissa A. [UNESP] (Elsevier, 2024)
This study investigates the molecular-level assembly and electronic properties of Langmuir and Langmuir–Schaefer (LS) films formed from Y6 (a non-fullerene electron acceptor) and PM6 (a wide bandgap electron donor polymer). We employ a variety of techniques including surface pressure-area isotherms, Brewster angle microscopy, ultraviolet-visible spectroscopy, Raman spectroscopy, and electrical characterizations to explore the behavior of these films. Our findings reveal that the films exhibit a tendency to aggregate and form non-homogeneous layers, which impacts their optical and electrical properties. The LS films show a significant sensitivity to solar radiation, which is evident from the changes in conductivity under illumination. This study highlights the potential of these materials in the development of photovoltaic applications, emphasizing the importance of molecular packing and film morphology in optimizing device performance.
Keywords: Electrical characterization; Langmuir film; Langmuir–Schaefer; Non-fullerene electron acceptor; Photovoltaics